The Impact of Government Policy on Macro Dynamic Innovation of the Creative Industries: Studies of the UK’s and China’s Animation Sectors - Zheng Liu (Journal of Open Innovation: Technology, Market and Complexity, 2021)
ABSTRACT: With digitalization and the support of policies, the creative industries have shown rapid growth in the last 20 years. Open forms of collective learning, user engagement and social networks have become popular to generate IPs and values. Meanwhile, government policy can support the sectors through subsidies, regulations, standardization, and protections at regional and national levels. This paper aims to explore the role of government policy in the innovation of creative industries from a macro dynamic perspective. The research method combines a structured literature review, a secondary document review of industry reports and government policy, and thematic content analysis. Through in-depth studies of the UK’s and China’s animation sectors, the paper identifies key elements of closed innovation, social innovation, and open innovation systems in the market. Comparisons of national government policies since 2000 reveal different approaches for countries where creative sectors are well-established, and for those starting with limited knowledge resources. A dynamic model is developed to address the evolution of macro dynamic innovation systems and the role of policies as interactive mechanisms. Practical implementation and future research areas are also suggested.